Comprehensive Guide to AI Software Design: From Conception to Implementation - Anup Kumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article presents a comprehensive examination of artificial intelligence software development, covering design principles, implementation strategies, and deployment practices. The article explores the convergence of traditional software engineering with advanced AI methodologies, addressing critical aspects including intelligence gathering, business process integration, and technology selection frameworks. The article delves into domain-specific applications across healthcare, financial services, and retail sectors while analyzing technical considerations in machine learning infrastructure, natural language processing, and computer vision systems. The article further examines bias mitigation strategies, system limitations, and best practices for production deployment, offering insights into monitoring, security, and scalability considerations for AI implementations.
Keywords: Artificial Intelligence Software Development; Machine Learning Infrastructure; Bias Mitigation; System Scalability; Production Deployment